Major Conflicts during the Transformation of the Rural Village Sŏnch’ŏn into a “Kingdom of Christianity” in Korea, 1896–1930 - Oak, Sung-Deuk (Journal of Korean religions, 2022)
Among the most Christianized cities and towns in northwest Korea (P’yŏngan-do and Hwanghae-do provinces) around 1925, Pyongyang was called the “Jerusalem of Chosŏn,” Chaeryŏng the “Christian world,” and Sŏnch’ŏn in P’yŏnganbuk-do a “kingdom of Christianity.” From 1915, half the population of Sŏnch’ŏn was identified as Christian (Presbyterian) and the Christian influence dominated town life. This article discusses the metamorphosis of Sŏnch’ŏn from an unknown small rural “heathen” town to a “kingdom of Christianity” within a generation. After describing the process and visualizing the spatial features of this transformation, it focuses on diverse inter-group conflicts, the discourse of the “kingdom of Christianity,” and socialists’ backlash against such triumphalism., By reviewing the history of the growth of Sŏnch’ŏn as a Christian city and major conflicts in its transformation, this case study of Northwestern Protestantism in Korea reveals the following three main points. First, the center of gravity of Korean Protestantism migrated from Seoul to Pyongyang in the 1900s and then to Sŏnch’ŏn in the next decade. Second, the nature of Northwestern Protestantism shifted from confrontation against Korean folk beliefs like shamanism in 1900s, to Christian nationalism against Japanese imperialism up to 1919, and then to Protestant capitalism against socialism in the 1920s. Their evangelical belief in the Christian superiority to traditional religions, political activism, economic middle-class status, and theological fundamentalism became the legacy of Northwestern Christians who engaged in the nation-building of the Republic of Korea from 1945 to the 1960s.